2021
DOI: 10.1002/dac.4803
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive multiple access assists multiple users over multiple‐input‐multiple‐output non‐orthogonal multiple access wireless networks

Abstract: The works in this study examine three scenarios. The scenario (I) as a common scenario with the base station (BS) and users are equipped with multiple antennae over Nakagami-m fading channels. To improve system performance, the transmit antenna selection (TAS) and maximization of successive interference cancellation (max-SIC) framework are deployed. A novel cumulative distribute function (CDF) for the scenario (I) is proposed, and the outage probability (OP) in novel closed form can be obtained. It is challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(165 reference statements)
0
7
0
Order By: Relevance
“…The studies described the application of the max-SIC-minrate framework reported in [48], [49]. This study presents Algorithms 1 and 2, which are applied to the max-SICmin-rate framework to investigate the outage probability at the UAV and terminal devices.…”
Section: System Performance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The studies described the application of the max-SIC-minrate framework reported in [48], [49]. This study presents Algorithms 1 and 2, which are applied to the max-SICmin-rate framework to investigate the outage probability at the UAV and terminal devices.…”
Section: System Performance Analysismentioning
confidence: 99%
“…In a previous study, the authors assumed that the devices are arranged from the nearest device D 1 to the farthest device D N [49], [50] or from the nearest device D N to the farthest device D 1 [51] for simplicity. Therefore, the power allocation factors in [49], [50] follow the arrangement α 1 < . .…”
Section: A Design For a Max-sic-min-rate Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the concept of NOMA, the farthest device D N was allocated the biggest PA factor since the farthest device D N owned poorest CSI. Inspired by studies [21,37], the PA factor α i for i = {N, . .…”
Section: Formulationsmentioning
confidence: 99%
“…Applied to all beyond 5G/6G wireless communications, nonorthogonal multiple access (NOMA) provides massive connections, low latency and high reliability [ 14 , 17 , 18 , 19 , 20 , 21 ]. In the current study, we took advantage of NOMA’s benefits, applying NOMA at the UAV to superimpose coding of the data received from wireless sensors and to forward this superimposed signal to a mobile data centre.…”
Section: Introductionmentioning
confidence: 99%